Sistem Pendukung Keputusan Pemilihan Rumput Terbaik untuk Pembuatan Taman Menggunakan Metode Vikor: - Anita Shintya Devi; Akim M.H. Pardede; Katen Lumbanbatu (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
A park in a limited sense is a plot of land that is arranged in such a way that it has beauty and comfort, and security for the owner or user. Based on the scale and shape, the park can be called a garden, park, or landscape. Now the park is not only filled with plants or large trees but also varies, one of which is by making ornamental grasses. A decision support system is used in the type of grass to make it easier for users to decide which grass to use for gardening. The VIKOR method is a Multi-Criteria Decision Making (MCDM) method that can be used to select more than one criteria. it can be seen that the first alternative which is the best choice of grass for gardening is peking, swiss and pescue grass with a value of Q = -0.6 and 0.05 and has the right to be recommended as a type of grass for gardening. Keywords: Park, Vikor Method, Decision Making System